Grounds of Engagement: Apartheid-Era African American and South African Writing - Robolin, Stéphane (The new black studies series, 2015)
Part literary history, part cultural study, Grounds of Engagement examines the relationships and exchanges between black South African and African American writers who sought to create common ground throughout the antiapartheid era. Stéphane Robolin argues that the authors' geographic imaginations crucially defined their individual interactions and, ultimately, the literary traditions on both sides of the Atlantic. Subject to the tyranny of segregation, authors such as Richard Wright, Bessie Head, Langston Hughes, Gwendolyn Brooks, Keorapetse Kgositsile, Michelle Cliff, and Richard Rive charted their racialized landscapes and invented freer alternative geographies. They crafted rich representations of place to challenge the stark social and spatial arrangements that framed their lives. Those representations, Robolin contends, also articulated their desires for black transnational belonging and political solidarity. The first book to examine U.S. and South African literary exchanges in spatial terms, Grounds of Engagement identifies key moments in the understudied history of black cross-cultural exchange and exposes how geography serves as an indispensable means of shaping and reshaping modern racial meaning.